2016
DOI: 10.1093/toxsci/kfw111
|View full text |Cite
|
Sign up to set email alerts
|

From the Cover: Exposing Imidacloprid Interferes With Neurogenesis Through Impacting on Chick Neural Tube Cell Survival

Abstract: As a neonicotinoid pesticide, imidacloprid is widely used to control insects in agriculture and fleas on domestic animals. However, it is not known whether imidacloprid exposure negatively affects neurogenesis during embryonic development. In this study, using a chick embryo model, we investigated the effects of imidacloprid exposure on neurogenesis at the earliest stage and during late-stage embryo development. Exposing HH0 chick embryos to imidacloprid in EC culture caused neural tube defects (NTDs) and neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 46 publications
3
8
0
Order By: Relevance
“…A decrease in the expression of EMT‐related adhesion molecules ( Cad6B , E‐Cadherin , and N‐cadherin ) in the NC was also observed. In agreement with these findings, imidacloprid reduced the expression of Shh and Bmp4 in the chick neural tube, with a failure of neural tube closure (Liu et al, ). Imidacloprid affects the thyroid follicles, pituitary gland, estrogen, and also has an adipogenic effect on birds (Pandey & Mohanty, ).…”
Section: Chemical Agentssupporting
confidence: 53%
“…A decrease in the expression of EMT‐related adhesion molecules ( Cad6B , E‐Cadherin , and N‐cadherin ) in the NC was also observed. In agreement with these findings, imidacloprid reduced the expression of Shh and Bmp4 in the chick neural tube, with a failure of neural tube closure (Liu et al, ). Imidacloprid affects the thyroid follicles, pituitary gland, estrogen, and also has an adipogenic effect on birds (Pandey & Mohanty, ).…”
Section: Chemical Agentssupporting
confidence: 53%
“…Goyal et al reported that TH induced neurological disorders in Gallus domesticus associated with brain histopathological changes [ 56 ]. Similarly, imidacloprid treatment inhibited both AChE and acetylcholine receptors, negatively affected neurogenesis during embryonic development of chicks, reduced cell proliferation, increased cell apoptosis, and altered the brain histoarchitecture [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Imidacloprid and fipronil had deleterious effects on growth of birds, exhibited as growth retardation, reduced weight gain and lost body condition, often as a consequence of reduced food intake (Hussein et al 2014a, b;Khalil et al 2017;LopezAntia et al 2015b). During embryonic development of birds, exposure to imidacloprid caused heart malformation , neural tube defects (Liu et al 2016;Wang et al 2016b), altered organ mass, and other anatomical deformities (Gobeli et al 2017). In red-legged partridges, exposure to imidacloprid led to a depressed immune response in offspring of treated parents (Lopez-Antia et al 2015a) and of parents and offspring when exposed to fipronil (Lopez-Antia et al 2015b).…”
Section: Sublethal Effectsmentioning
confidence: 99%